The Influence of Job Satisfaction as a Moderating Variable on the Productivity of Craftsmen by Competence and Work-Life Balance - Padme, Ni Luh Ayu; Ibrahim, Isra Dewi Kuntary; Yuliana, Ika (ProBisnis : Jurnal Manajemen, 2024)
Small and medium enterprises (SMEs) were experiencing an increasing trend in the productivity of their craftsmen. This study investigated the impact of work-life balance and competence on productivity, with job satisfaction serving as a moderating variable. The sample size was 133, and the study population was 200. Probability sampling techniques were employed using SmartPLS 3.0. The study's findings indicated that productivity was significantly and positively impacted by work-life balance and competence. The relationship between competence and productivity was bolstered by job satisfaction, while the relationship between work-life balance and the productivity of Mawar Ketak craftsmen was weakened.